2017
DOI: 10.1016/j.ahj.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and the risk of hospitalization and death in atrial fibrillation: A population-based study

Abstract: Background Patients with atrial fibrillation (AF) have many comorbidities and excess risks of hospitalization and death. Whether the impact of comorbidities on outcomes is greater in AF than the general population is unknown. Methods 1430 AF patients and community controls matched 1:1 on age and sex were obtained from Olmsted County, Minnesota. Andersen-Gill and Cox regression estimated associations of 19 comorbidities with hospitalization and death, respectively. Results AF cases had a higher prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 33 publications
7
76
2
2
Order By: Relevance
“…We also found that, given the same multimorbidity status, younger age groups tended to be admitted more often but older age groups tended to spend more days in hospital. As far as we know, this is the first Asian study that investigated the impact of multimorbidity over a follow-up period of more than five years [13,[25][26][27][28][29]. Our findings agreed with a previous study showing a negative age moderation effect of multimorbidity and short-term hospitalization outcomes [14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that, given the same multimorbidity status, younger age groups tended to be admitted more often but older age groups tended to spend more days in hospital. As far as we know, this is the first Asian study that investigated the impact of multimorbidity over a follow-up period of more than five years [13,[25][26][27][28][29]. Our findings agreed with a previous study showing a negative age moderation effect of multimorbidity and short-term hospitalization outcomes [14].…”
Section: Discussionsupporting
confidence: 90%
“…Existing research on multimorbidity in middle age is limited. Previous studies seldom followed up participants long enough to investigate the medium-or long-term impact of multimorbidity on adverse health outcomes and burden [13,[25][26][27][28][29]. Even fewer studies stratified by age group to study the moderating effect of age [14].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative AF is well-documented, with an incidence of 8%-50%, depending on the type and site of the surgery [212][213][214][215]. AF is responsible for increasing the postoperative hospital length of stay and is an independent predictor of mortality [3,216]. Although several observational studies have suggested a survival benefit following restoration of the sinus rhythm following cardiovascular surgery [213,215,217], the most recent RCT that studied the effectiveness and safety of rate control versus rhythm control after cardiothoracic surgery showed equal duration of hospital stay and complications [218].…”
Section: Arrhythmia Management For Post-operative Atrial Fibrillationmentioning
confidence: 99%
“…Some studies have revealed that multimorbidity is significantly more prevalent in patients with AF than in those without AF. 21 Multimorbidity is also associated with worse survival of patients with AF, 21,22 and AF patients with multimorbidity have higher stroke and bleeding risk. The abovementioned findings should be related to prioritizing patients with AF and multimorbidity for optimal management according to the ABC pathway.…”
Section: Adherence To Cardiovascular and Comorbidity Risk Man-mentioning
confidence: 99%